Successful Treatment and Management of Canine Ehrlichiosis-Leishmaniosis-Heartworm Comorbidity - Leal-Lima, Adam; Ferreira, Tiago Cunha; Ferreira, Társsila Mara Vieira; Coelho, Pedro Covas; Nunes-Pinheiro, Diana Célia Sousa (Acta Scientiae Veterinariae, 2021)
Background: Canine vector borne diseases (CVBD) are common in tropical countries where the climate favors arthropods abundance. Comorbidity with one or more CVBD are reported as clinical complication and worsen prognostic. Canine visceral leishmaniosis (CanL) is an endemic zoonotic disease in Brazil caused by Leishmania infantum, with several restrictions to canine treatment and suggestion of reservoirs euthanasia for disease control. Heart worm (HW) is a helminthic disease caused by Dirofilaria immitis infection in dogs. It is a chronic heart disease, which can lead to death by congestive heart failure. Canine ehrlichiosis (CE) is caused by Ehrlichia canis bacterial infection with a zoonotic potential and fatal to dogs in acute and chronic presentations. Exposed the above, this study aims to describe a successful treatment and management of a dog with CanL, CE, and HW comorbidity. Case: A 3-year-old male uncastrated black Labrador dog, weighing 35 kg, was admitted to the veterinary clinic due to immunochromatographic CanL positive test performed by municipal zoonosis control center active surveillance in August 2014. Clinical exam showed a mild shedding, intermittent eye white/yellow discharge and popliteal lymph nodes enlargement. After positive for CanL, veterinary requested more laboratorial exams. IFAT and ELISA were positive for CanL, blood smear showed presence of microfilaria, and bone marrow cytology showed Ehrlichia spp. morulae and microfilaria. Initial treatment prescribed was oral doxycycline, omeprazole, ranitidine, and domperidone for 30 days, and allopurinol and ivermectin until further recommendation. Additionally, repellent collar, repellent spray and vitamin supplement was indicated. After first month, marbofloxacin for 30 days and three doses of immune stimulant protocol were administrated. After three months of treatment, dog still positive for heartworm, ehrlichiosis, and CanL. Doxycycline protocol was repeated. Dog became consistently negative for all pathogens one year later with persistent thrombocytopenia but without clinical signs, ergo allopurinol and ivermectin were discontinued. After four years of follow up, the animal had an acute pancreatitis and died, with unremarkable total blood count and negative for all pathogens. Discussion: CVBD coinfections are commonly reported as worsen prognostic in endemic regions. The pathogens reported here share a host immunomodulation competence. L. infantum and Ehrlichia spp.downregulates Th1 response, whereas D. immitis increase as Th2 profile. The therapeutic protocol was iniciated by staging CanL. Since the patient had clinical signs, allopurinol was prescribed as a well-established drug for CanL. Marbofloxacin was added due to its high safety drug in clinical improvement of infected dogs with and without renal disease and in vitro effectiveness against L. infantum. Domperidone was used to promote Th1 cytokine profile as INF-γ, IL-2, IL-12, and TNF-α. We used an immunostimulant protocol to favor polarization to the Th1 profile comprised by 30 days of domperidone protocol followed by a vaccine and an immunomodulator. Doxycycline was used successfully for Ehrlichia spp. and HE clearance after two treatment courses and one year of ivermectin every 15 days. The animal presented intermittent coughing episodes on the first treatment course, but no medical intervention was needed besides exercise restriction. Our report shows the successful management of one dog with CanL, CE and HE comorbidity. This success was possible due to early detection and good therapeutic choice. Keywords: canine visceral leishmaniosis, coinfection, Dirofilaria immitis, Erhlichia canis, Leishmania infantum, treatment.